AMBIGUOUS STIMULUS IN THE EDUCATIONAL PROCESS OF PUPILS WITH HEARING IMPAIRMENT - Petra Potměšilová; Buqiong (Paidagogos - Society For Philosophy, Theory and Praxis of Education, 2015)
Hearing impairment has a major influence on the person with such impairment. The hearing impairment is the most frequently mentioned impact on communication skills and related skills such as working with concepts and symbols ambiguous stimuli. (Potměšil, 2009; Horáková, 2012; Souralová, 2002; Potměšilová, 2014; Lamprapoulou, 2003; Marschark ,1997) One option to reduce this negative impact is usage of classifying functional processes in the educational process. One of these approaches can be art-philetics.